Implementation of Teaching Factory to Improve Student Competence and Innovation at State Vocational High School 4 Lhokseumawe - angga, Danu; Fatwa, Islami; Siraj; Jumadi; Abubakar (MANDAILING GLOBAL EDUKASIA, 2024)
This research is a qualitative study aimed at understanding the role of human resource aspects, partnership aspects, and product aspects in supporting teaching factory learning in the expertise competency of light vehicle engineering at SMK Negeri 4 Lhokseumawe. The research was conducted at SMK Negeri 4 Lhokseumawe, Lhokseumawe Regency, Aceh Province. The data sources were obtained from primary and secondary sources. The data collection methods included interviews with several students and teachers, followed by direct observation at SMK Negeri 4 Lhokseumawe to examine the application of the teaching factory learning model. Documentation of each activity was also conducted. The data collection instruments consisted of questionnaires that were distributed to students and teachers. The research results regarding the human resource aspect showed that the highest frequency value was 17 individuals in the good category, with a percentage of 65.38%. For the partnership aspect, the highest frequency value was 12 individuals in the very good category, with a percentage of 85.71%. Lastly, for the product aspect, the highest frequency value was 7 individuals in the very good category, with a percentage of 100%. Based on these findings, it can be concluded that the human resource aspect, partnership aspect, and product aspect play a very good role in the implementation of the teaching factory in the light vehicle engineering expertise competency at SMK Negeri 4 Lhokseumawe.